Pemanfaatan Sari Kulit Buah Naga sebagai Upaya Peningkatan Nilai Fisik dan Sensori pada Permen Jelly Sari Tempe - Siswi Sekar Sari; Nurrahman Nurrahman; Nurhidajah Nurhidajah (Jurnal Pangan dan Gizi, 2021)
Dragon fruit skin is organic waste which has high content of vitamin C, pectin and anthocyanin and can be used as raw material for making jelly candy because pectin is one of the gelling agent and anthocyanin is a natural dye that can make sari tempe jelly candy more interesting. The aim of this research is to determine the effect of adding the dragon fruit peels extract(10,20,30, and 40%),  towards the dissolved solids, elasticity, antioxidant activity, and sensory properties in jelly candies from extract of tempe.Then, there was physical testing (the amount of dissolved solids and elasticity), and sensory properties (aroma, taste, color, and texture). The result of the research showed that the addition of the concentration of dragon fruit skin extract on jelly candies of tempe extract had very significant effect on dissolved solids, elastisity, color, and texture, but there were not significantly different from aroma and its taste. The best treatment was in the addition of 40% extract of dragon fruit skin.